2015
DOI: 10.1371/journal.ppat.1005263
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Inhibits Ebola Virus Infection

Abstract: Ebola virus outbreaks, such as the 2014 Makona epidemic in West Africa, are episodic and deadly. Filovirus antivirals are currently not clinically available. Our findings suggest interferon gamma, an FDA-approved drug, may serve as a novel and effective prophylactic or treatment option. Using mouse-adapted Ebola virus, we found that murine interferon gamma administered 24 hours before or after infection robustly protects lethally-challenged mice and reduces morbidity and serum viral titers. Furthermore, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
102
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 96 publications
(116 reference statements)
10
102
0
1
Order By: Relevance
“…Tilorone gave a 50% effective concentration (EC 50 ) of 230 nM (35), making it one of the most potent small-molecule inhibitors of EBOV reported. This result is also consistent with reports showing IFN-inhibits EBOV infection (37).…”
supporting
confidence: 93%
“…Tilorone gave a 50% effective concentration (EC 50 ) of 230 nM (35), making it one of the most potent small-molecule inhibitors of EBOV reported. This result is also consistent with reports showing IFN-inhibits EBOV infection (37).…”
supporting
confidence: 93%
“…8C and D). However, in the case of Ebola virus, postchallenge treatment was more efficacious (53), and other studies have shown that multiple treatments with IFN-␥ protected mice from a lethal challenge with vaccinia virus via the respiratory route (71). EHV-1 infection did not cause a decrease in the viability of IFN-␥-treated MH-S alveolar macrophages (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…Severe murine lung immunopathology elicited by RacL11 correlated with early production of macrophage inflammatory proteins 1␣, 1␤, and 2 and tumor necrosis factor alpha (23). In a cell culture model of Ebola virus infection of mouse macrophages, murine IFN-␥ provided Ͼ95% protection with a dose of only 2 ng/ml (53). EHV-1 KyA and RacL11 were able to replicate in MH-S murine alveolar macrophages, and the EHV-1 regulatory proteins IEP (immediate early protein) and EICP0 were expressed at 6 hpi ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…IFN-␤, used for treatment at an early time postexposure, was effective in prolonging the survival time of rhesus macaques but did not improve the survival rate (23). Another study revealed that IFN-␥ had significant anti-EBOV effects in vivo (24). One recent in vitro study found that type I IFNs showed efficacy in pretreatments performed 24 h before viral infection at a low multiplicity of infection (MOI), while IFN-␥ showed even lower efficacy.…”
Section: Discussionmentioning
confidence: 99%